Sex‐specific evolution of a Drosophila sensory system via interacting cis‐ and trans‐regulatory changes. Issue 1 (3rd March 2022) - Luecke, David; Rice, Gavin; Kopp, Artyom
Abstract: The evolution of gene expression via cis ‐regulatory changes is well established as a major driver of phenotypic evolution. However, relatively little is known about the influence of enhancer architecture and intergenic interactions on regulatory evolution. We address this question by examining chemosensory system evolution in Drosophila . Drosophila prolongata males show a massively increased number of chemosensory bristles compared to females and males of sibling species. This increase is driven by sex‐specific transformation of ancestrally mechanosensory organs. Consistent with this phenotype, the Pox neuro transcription factor ( Poxn ), which specifies chemosensory bristle identity, shows expanded expression in D. prolongata males. Poxn expression is controlled by nonadditive interactions among widely dispersed enhancers. Although some D. prolongata Poxn enhancers show increased activity, the additive component of this increase is slight, suggesting that most changes in Poxn expression are due to epistatic interactions between Poxn enhancers and trans ‐regulatory factors. Indeed, the expansion of D. prolongata Poxn enhancer activity is only observed in cells that express doublesex ( dsx ), the gene that controls sexual differentiation in Drosophila and also shows increased expression in D. prolongata males due to cis ‐regulatory changes. Although expanded dsx expression may contribute to increased activity of D. prolongata Poxn enhancers, this interaction is not sufficient to explain the full expansion of Poxn expression, suggesting that cis – trans interactions between Poxn, dsx, and additional unknown genes are necessary to produce the derived D. prolongata phenotype. Overall, our results demonstrate the importance of epistatic gene interactions for evolution, particularly when pivotal genes have complex regulatory architecture. Abstract : Leg bristles in male Drosophila prolongata have evolved from mechanosensory to chemosensory function, due to changes in gene regulatory sequences for the sensory‐specifying gene Poxn and changes in patterning gene expression including the sex specifier dsx . Research Highlights: In Drosophila prolongata males, many mechanosensory organs are transformed into chemosensory organs. This is due in part to interacting regulatory changes in Poxn, which controls chemosensory organ development, and dsx, which controls sexual differentiation.